Elaboration of the Al-Al3Ni Alloy Eutectic by a Carbothermal Process - Imane Bahaj; Mohammed Kaddami; Mohamed Essahli (The Scientific World Journal)
The present study develops an elaborate method of materials Al-Al3Ni by carbothermic reduction of nickel oxide from the decomposition of Ni(NO3)2.4H2O mixed with aluminum powder. This nitrate salt represents the source of nickel for an elaboration of these materials. The thermodynamic parameters adopted in the experimental study were defined based on the liquid-solid phase equilibrium diagram of the binary system Al-Ni and the Ellingham approach. Throughout this study, the metal Ni is elaborated by carbothermic reduction of nickel oxide resulting from nitrate salt decomposition at 900°C under a nitrogen atmosphere. The heat treatment at 900 °C of a mixture of nitrate salt with aluminum powder under an inert gas atmosphere leads to the formation of phases Al2O3, Al4C3, Al, and Ni. The annealing of these obtained phases during 1 h and under a nitrogen flow atmosphere at the temperature of 600°C allowed us to obtain the Al-Al3Ni alloy devoid of oxides. The characterization of these obtained solid phases was carried out by the XRD analysis, the SEM-EDS, the DTA, and the DSC.